Discovery of Rickettsia spp. in mosquitoes collected in Georgia by metagenomics analysis and molecular characterization - Pollio, Adam R.; Jiang, Ju; Lee, Sam S.; Gandhi, Jaykumar S.; Knott, Brian D.; Chunashvili, Tamar; Conte, Matthew A.; Walls, Shannon D.; Hulseberg, Christine E.; Farris, Christina M.; Reinbold-Wasson, Drew D.; Hang, Jun (Frontiers in Microbiology, 2022)
Arthropods have a broad and expanding worldwide presence and can transmit a variety of viral, bacterial, and parasite pathogens. A number of Rickettsia and Orientia species associated with ticks, fleas, lice and mites have been detected in, or isolated from, febrile illness patients and/or animal reservoirs throughout the world. Mosquitoes are not currently considered vectors for Rickettsia spp. pathogens to human or to animals. In this study, we conducted random metagenome next-generation sequencing (NGS) of 475 pools of Aedes, Culex, and Culiseta species mosquitoes collected in the country of Georgia from 2018 – 2019, identifying rickettsial gene sequences in 33 pools of mosquitoes. We further confirmed the findings of Rickettsia genus by species specific quantitative PCR (qPCR) and multi locus sequence typing (MLST). The NGS and MLST results indicate detected Rickettsia spp. are closely related with Rickettsia bellii, not known to be pathogenic in humans. The results, together with other reports of Rickettsia spp. in mosquitoes and the susceptibility and transmissibility experiments, suggest mosquitoes may play a role in the transmission cycle of Rickettsia spp.